The field of intelligence study in academic institutions: A comparative analytical study of American and British intelligence studies - Ibrahim, Mohamed Elzin Mohamed Ahmed (Arab Journal for Sciences and Research Publishing, 2024)
This paper presents a theoretical approach to the study of intelligence in the United States and the United Kingdom, examining the academic nature of intelligence teaching and its scientific approaches. It is based on the premise that the increasing role played by intelligence has accelerated the process of academicization. As the demand for intelligence practitioners increased, American and British universities responded to the growing need to formulate academic programs dedicated to intelligence. The study is based on the use of several approaches, but mainly the historical, comparative and situational approaches to address the research problem. The problem revolves around a main question: To what extent have intelligence specialists in America and Britain been able to reach approaches that are considered a basis of knowledge and an academic field? The study reached several results, the most important of which was that intelligence took its position as a scientific, professional, academic field, and that the American approach is influenced by the social sciences, while the British approach focuses on history. The study recommended seeking to expand intelligence studies as an academic field in the Arab world and allocating programs to study and teach intelligence in Arab universities.